2016
DOI: 10.1002/micr.30095
|View full text |Cite
|
Sign up to set email alerts
|

The maxillary artery as a recipient vessel option for complex midface and anterior skull base microsurgical repair: A cadaveric study

Abstract: In situations where primary recipient vessel sites are unavailable, the maxillary artery represents an innovative option to be considered with suitable recipient artery characteristics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Based on a recent retrospective cohort study of 31 patients, Hanick et al [66] reported the use of the angular vessels as a viable option for microvascular anastomosis in head and neck reconstruction. Despite smallercaliber vessels, the angular artery and vein can be advantageous for ASB defects due to their proximity to the sinonasal cavity and shorter pedicle requirements.…”
Section: Recipient Vesselsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on a recent retrospective cohort study of 31 patients, Hanick et al [66] reported the use of the angular vessels as a viable option for microvascular anastomosis in head and neck reconstruction. Despite smallercaliber vessels, the angular artery and vein can be advantageous for ASB defects due to their proximity to the sinonasal cavity and shorter pedicle requirements.…”
Section: Recipient Vesselsmentioning
confidence: 99%
“…Despite smallercaliber vessels, the angular artery and vein can be advantageous for ASB defects due to their proximity to the sinonasal cavity and shorter pedicle requirements. This vascular supply can also be beneficial in the setting of previously failed reconstructions or irradiation to the neck [66] . Other potential recipient vessels that have been described based on cadaveric studies include the superior trochlear system [23] .…”
Section: Recipient Vesselsmentioning
confidence: 99%
“…8,10 In a cadaver study with 17 specimens, Assam et al described the use of the third segment of the maxillary artery as a potential recipient vessel for free flap reconstruction of the midface or skull base. 12 In another cadaver study, Reyes et al described the use of a fascia lata free flap anastomosed to the superior trochlear system for reconstruction of the skull base. 13 The recipient vessels were identified via a Lynch incision, and the fascia lata free flap was introduced through the nose.…”
Section: Vessel Options For Microvascular Anastomosismentioning
confidence: 99%